HEALING THROUGH WORDS: PSYCHOLOGICAL RESILIENCE AND MENTAL WELL-BEING IN INDIAN CLASSICAL LITERATURE - Khanna, Pooja; Deswal, Neerja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper seeks to explore psychological aspects of Indian classical literature. To this end, it avails an interdisciplinary lens linking ancient wisdom with modern mental health discourse. Relying on texts like the Bhagavad Gita, Ramayana, Mahabharata, and Vedas, the paper demonstrates how concepts like karma yoga, dhyana, vairagya, and bhakti provide frameworks for emotional resilience, self-regulation, and existential insight. The study emphasizes the pedagogical and therapeutic relevance of these texts in modern education, psychology, and cultural studies. Through a comparative analysis with Western psychological models, this paper adopts a pluralistic, decolonized approach to well-being, which corroborates Indian literature as a reservoir of holistic healing and self-knowledge.